Janus Kinase Inhibitor Tofacitinib Shows Potent Efficacy in a Mouse Model of Autoimmune Lymphoproliferative Syndrome (ALPS) - Yokoyama, Seiji (J Clin Immunol, 2015)
PURPOSE: Autoimmune lymphoproliferative syndrome (ALPS) is a non-malignant genetic disorder of lymphocyte homeostasis with defective Fas-mediated apoptosis. Current therapies for ALPS primarily target autoimmune manifestations with non-specific immune suppressants with variable success thus highlighting the need for better therapeutics for this disorder. METHODS: The spectrum of clinical manifestations of ALPS is mirrored by MRL/lpr mice that carry a loss of function mutation in the Fas gene and have proven to be a valuable model in predicting the efficacy of several therapeutics that are front-line modalities for the treatment of ALPS. We evaluated the potential efficacy of tofacitinib, an orally active, pan-JAK inhibitor currently approved for rheumatoid arthritis as a single agent modality against ALPS using MRL/lpr mice. RESULTS: We demonstrate that a 42-day course of tofacitinib therapy leads to a lasting reversal of lymphadenopathy and autoimmune manifestations in the treated MRL/lpr mice, Specifically, in treated mice the peripheral blood white blood cell counts were reversed to near normal levels with almost a 50 % reduction in the TCRαβ(+)CD4(−)CD8(−)T lymphocyte numbers that coincided with a parallel increase in CD8(+) T cells without a demonstrable effect on CD4(+) lymphocytes including FoxP3(+) regulatory T cells. The elevated plasma IgG and IgA levels were also drastically lowered along with a significant reduction in plasmablasts and plasmacytes in the spleen. CONCLUSION: On the basis of these results, it is likely that tofacitinib would prove to be a potent single agent therapeutic modality capable of ameliorating both offending lymphadenopathy as well as autoimmunity in ALPS patients.